2019
DOI: 10.1007/s00415-019-09596-3
|View full text |Cite
|
Sign up to set email alerts
|

“Smoking paradox” is not true in patients with ischemic stroke: a systematic review and meta-analysis

Abstract: Background Ischemic stroke (IS) is a common cause of death from vascular diseases. Studies have found that smoking increases the risk of ischemic stroke, but the association of smoking with the outcome of IS remains unclear. This metaanalysis aims to investigate the effect of smoking on the prognosis of IS. Methods We searched four electronic databases including PubMed, EMBASE, Cochrane library and Web of science for papers, published before January 2019. In this meta-analysis, Review Manager 5.3 software was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
(39 reference statements)
1
13
0
Order By: Relevance
“…Smoking had a protective effect. The “smoking paradox” on ischemic stroke outcome, however, was not confirmed in a recent meta-analysis [13]. As expected, increasing stroke severity in terms of NIHSS on admission was associated with worse outcome at 90 days.…”
Section: Discussionmentioning
confidence: 93%
“…Smoking had a protective effect. The “smoking paradox” on ischemic stroke outcome, however, was not confirmed in a recent meta-analysis [13]. As expected, increasing stroke severity in terms of NIHSS on admission was associated with worse outcome at 90 days.…”
Section: Discussionmentioning
confidence: 93%
“…29 The results of this study indicate that had smoking history is a protective factor of disability among the elderly with stroke may be due to the effects of passive smoking which were not examined in this study. 30 After controlling for other variables, there was a significant relationship between joint disease status with disability among elderly with stroke The adjusted prevalence ratio (aPR) result was 0.546 (CI 95%= 0.311-0.958), shows that had joint disease was the protective factor of disability among elderly with stroke. This research was not in line with research in England 31 which states that musculoskeletal symptoms are common in people with stroke and have a significant additional effect on the disability of stroke sufferers.…”
Section: Discussionmentioning
confidence: 95%
“…Smoking increases the risk of stroke in the short term by promoting thrombosis [42] and reducing cerebral blood flow via arterial vasoconstriction [43]. However, the thrombotic process can be reversible [44], and cerebral blood flow can significantly improve soon after quitting [25,39,45,46]. It is also possible that our AIS-HF population 65-74 with a previous smoking history showed a lower stroke severity returned to nonsmoking status, and might have quit smoking for a significant period following the onset of AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Although smoking is an apparent risk factor for AIS, some studies [31,37,38]have found an association between smokers that receive thrombolytics and improved clinical outcomes. The most common critique of studies that affirm the paradox is their small sample size [39], and most metanalyses find no association between smoking status and stroke severity [40,41]. The risk of stroke is reported to decrease after 2 to 4 years of smoking cessation and returns to the level of non-smoking status after five years of smoking cessation [25] .…”
Section: Discussionmentioning
confidence: 99%